A Three‐Dimensional M3AB‐Type Hybrid Organic–Inorganic Antiperovskite Ferroelectric: [C3H7FN]3[SnCl6]Cl. Issue 72 (26th November 2019) - Li, Guo‐Ping; Lu, Si‐Qi; Chen, Xin; Liao, Wei‐Qiang; Tang, Yuan‐Yuan; Xiong, Ren‐Gen
Abstract: Since the first perovskite CaTiO3 was discovered in 1839, the development of perovskite has a history of 180 years. The emergence of solar cells (CH3 NH3 )PbI3 has set off the trend of hybrid organic–inorganic perovskite (HOIP) materials. Since then, various HOIPs have sprung up and been widely used in various material devices. Among them, HOIP ferroelectrics have gained widespread attention. However, antiperovskite, as a twin brother of perovskite, has been neglected although it has similar structure with perovskite. Here, we successfully found that [C3 H7 FN]3 [SnCl6 ]Cl has a three‐dimensional (3D) antiperovskite structure with the formula M3 AB. Importantly, the compound exhibits obvious ferroelectric properties with an Aizu notation of 622F6 at 391 K. To the best of our knowledge, this is the first 3D hybrid organic–inorganic antiperovskite ferroelectric, which will greatly promote the development of antiperovskite families with more superior physical properties. Abstract : Twin brothers : By the organic–inorganic hybrid molecular design strategy, the first three‐dimensional organic–inorganic hybrid antiperovskite ferroelectric [C3 H7 FN]3 [SnCl6 ]Cl, which exhibits ferroelectric properties, was synthesized.